Effects and mechanisms of decabromodiphenyl ethane on Chlorella sorokiniana: Transcriptomics, proteins and fatty acid production. (November 2022) - Wang, Wenjing; Sheng, Yanqing
Abstract: Decabromodiphenyl ethane is a novel brominated flame retardant, that has always been dissolved in organic solvents to explore its activities on aquatic organisms. In this study, the influences of decabromodiphenyl ethane on the microalga Chlorella sorokiniana ( C. sorokiniana ) were studied, and three microalgae treatments, including decabromodiphenyl ethane dissolved in dimethyl sulfoxide solvent (DBDPE treatment), dimethyl sulfoxide alone (control II) or untreated (control I) were used in the experiment, respectively. The results showed that the growth of C. sorokiniana was remarkably enhanced in the DBDPE treatment compared with the control I and II groups. Conjoint analysis of transcriptomics and quantitative proteome displayed that the upregulated differentially expressed genes and proteins of DBDPE:control I were enriched in 6 pathways, and downregulated genes/proteins of DBDPE:control I were enriched in 3 pathways. The upregulated differentially expressed genes and proteins of DBDPE:control II were enriched in 4 pathways, and downregulated genes/proteins of DBDPE:control II were enriched in 6 pathways. In addition, decabromodiphenyl ethane changed the fatty acid concentration in C. sorokiniana cells. The activities of superoxide dismutase were enhanced when C. sorokiniana were treated by decabromodiphenyl ethane. The data highlighted that the mRNA and protein expression relating to the fatty acid production, of C. sorokiniana were significantly affected by decabromodiphenyl ethane, and decabromodiphenyl ethane pollution changed the physiological metabolism of microalgae and had harmful effects on natural environments. Highlights: Decabromodiphenyl ethane affects Chlorella sorokiniana growth. Decabromodiphenyl ethane reduces fatty acid productions of phytoplankton. Dimethyl sulfoxide negatively affects gene expression and protein production in C. sorokiniana. Dimethyl sulfoxide control and a blank control were necessary for the deterimination.